Influence of a Crosslinker Containing an Azo Group on the Actuation Properties of a Photoactuating LCE System - Braun, Lukas B. (Polymers (Basel), 2016)
Photoactuating liquid crystalline elastomers (LCE) are promising candidates for an application as artificial muscles in microdevices. In this work, we demonstrate that by optimizing (1) the illumination conditions and (2) the mixture of azo monomer and azo crosslinker, thick films of an all-azo LCE can be prepared, which show a strong length change without bending during photoactuation. This becomes possible by working with white light (about 440 nm), whose absorption is low, leading to a large penetration depth. By adding an azo crosslinker to a previously prepared system, several improvements of the actuation properties—like a stronger photoactuation at lower operational temperatures—could be achieved. In addition, films of different crosslinker concentrations and thicknesses were produced by photopolymerization at varying temperatures within a magnetic field, and their thermo- and photoresponsive behavior was investigated. An extraordinarily strong maximal thermal actuation of 46% and—by exposure to white light at 70 °C—a photoresponsive change in length of up to 40% in just about 13 s could be obtained. Even densely crosslinked samples were still able to photoactuate remarkably. Isothermal back-deformation could either be achieved by irradiation with red light (7 min) or by keeping the film in the dark (13 min).